3D printed Styrax Liquidus (Liquidambar orientalis Miller)-loaded poly (L-lactic acid)/chitosan based wound dressing material: Fabrication, characterization, and biocompatibility results - (:unkn) unknown (My University, 2023)
The medicinal plant of Styrax liquidus (ST) (sweet gum balsam) which extracted from Liquidambar orientalis Mill tree, was loaded into the 3D printed polylactic acid (PLA)/chitosan (CS) based 3D printed scaffolds to investigate its wound healing and closure effect, in this study. The morphological and chemical properties of the ST loaded 3D printed scaffolds with different concentrations (1 %, 2 %, and 3 % wt) were investigated by Scanning Electron Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FT-IR), respectively. In addition, the mechanical and thermal properties of the materials were investigated by Tensile test and Differential Scanning Calorimetry (DSC), respectively. The antimicrobial activities of the ST loaded 3D printed scaffolds and their incubation media in the PBS (pH 7.4, at 37 °C for 24 h) were investigated on two Gram-positive and two Gram-negative standard pathogenic bacteria with the agar disc diffusion method. The colorimetric MTT assay was used to determine the cell viability of human fibroblast cells (CCD-1072Sk) incubated with free ST, ST loaded, and unloaded 3D printed scaffolds. The 1 % and 2 % (wt) ST loaded PLA/CS/ST 3D printed scaffolds showed an increase in the cell number. Annexin V/PI double stain assay was performed to test whether early or late apoptosis was induced in the PLA/CS/1 % ST and PLA/CS/2 % ST loaded groups and the results were consistent with the MTT assay. Furthermore, a wound healing assay was carried out to investigate the effect of ST loaded 3D printed scaffolds on wound healing in CCD-1072Sk cells. The highest wound closure compared to the control group was observed on cells treated with PLA/CS/1 % ST for 72 h. According to the results, novel biocompatible ST loaded 3D printed scaffolds with antimicrobial effect can be used as wound healing material for potential tissue engineering applications.
Keywords: Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; Yaşam Bilimleri (LIFE); BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Life Sciences (LIFE); MOLECULAR BIOLOGY & GENETICS; BIOCHEMISTRY & MOLECULAR BIOLOGY; Yapısal Biyoloji; Biyokimya; Moleküler Biyoloji; Structural Biology; Biochemistry; Molecular Biology; 3D printing; Controlled releasing; Styrax liquidus; Tissue engineering; Wound dressing; Wound healing